Satisfaction with analgesic therapy in patients with rheumatic diseases in real clinical practice, according to the KOMPAS study (Quality of Pain Relief in the Opinion of Patients with Arthritis and Back Pain) - E. Yu. Pogozheva; A. E. Karateev; N. A. Bulgakova; V. N. Amirdzhanova; E. S. Filatova; V. A. Nesterenko; A. M. Lila (Современная ревматология)
Patient's satisfaction with treatment is a fundamental indicator of the quality of medical care, which is especially important for assessing the effectiveness of therapy for musculoskeletal pain in rheumatic diseases (RD).Objective: to determine satisfaction of patients with RD with pain relief therapy and to analyze the factors influencing the subjective assessment of analgesic therapy.Patients and methods. Anonymous survey of 1040 patients (age 55.8±14.0 years, 76.8% were women) with RD, rheumatoid arthritis (RA), osteoarthritis (OA), spondyloarthritis, systemic connective tissue diseases and gout, was carried out. The presence of pain and its therapy, satisfaction with treatment, and patient's opinion about the reasons of low pain relief effectiveness were assessed. The dependence of the presence of dissatisfaction with treatment on a number of demographic and clinical factors was analyzed.Results and discussion. 71.5% of patients experienced pain in one or more joint areas and/or in the back. 70.6% of patients used non-steroidal antiinflammatory drugs (NSAIDs), 1.6% – paracetamol, 40.0% – non-drug modalities and methods of alternative medicine. 15.6% of the respondents were completely satisfied with the treatment, 64.0% were partially satisfied, and 20.4% were completely dissatisfied. The main subjective reasons for the insufficient effectiveness of analgesic therapy were: fear of taking prescribed medications due to possible complications (45.4%), low effectiveness of drugs (15.7%), insufficient attention of doctors (20.3%). Male gender, body mass index >30 kg/m2 , severe pain, pain in several areas, and the diagnosis of OA were statistically significantly associated with treatment dissatisfaction. In contrast, patients with RA showed greater satisfaction with treatment.Conclusion. Most patients with RD are dissatisfied with the results of pain therapy. Educational work with patients and a personalized approach to prescribing analgesic therapy is needed.